Characterization and physical mechanisms of aggregate stability in Ferrisols - ZHENG Xiao-ping; LU Sheng-gao (浙江大学学报. 农业与生命科学版, 2005)
The aggregate size distribution (PSD) and aggregate stability in Ferrisols were measured by Yoder's wet-sieving, mechanical shaking and chemical dispersion, and Le Bissonnais method. The aggregate stability indices as determined by the three methods were very significantly correlated with the clay content of Ferrisols. The amounts of aggregate with a diameter of>0.25 mm determined by wet-sieving and the mean weight diameter (MWD) determined by Le Bissonnais method were significantly correlated with organic matter content of Ferrisols. All the stability indices of aggregates of forest and orchard soils were higher than that of the other soils. The bare soil and soil-forming parent material had the lowest stability indices of aggregates. When ranked according to MWD in the three treatment of Le Bissonnais method, the order was WS>SW>FW. Fast wetting (FW) brought about the largest disruption while wet-stirring (WS) the least. This suggests that the basic mechanism of aggregate breakdown in Ferrisols lies in the shaking caused by the compression of air entrapped inside aggregates during wetting. The amounts and stability indices in Ferrisols can be taken as indicators for soil quality and soil antierodibilty.